The digital workforce and the workplace of the future - COLBERT, Amy (Institutional Knowledge at Singapore Management University, 2016)
The authors reflect on ways increased prevalence of technology and digital natives entering the workplace influence how work is approached. They talk about competencies of the digital workforce and suggests both digital natives and digital immigrants could have the skills needed to utilize technology for manipulating data, problem solving, and new product creation. They comment on interpersonal relating and identity development in digital work forces, and the utilization of technology at work.